The government and copyright : the government as proprietor, preserver and user of copyright material under the copyright act 1968 (Cth) - Gilchrist, John Steel (Sydney University Press, 2015)
The government and copyright' focuses on the interplay between law, policy and practice in copyright law by investigating the rights of the government as the copyright owner, the preserver of copyright material and the user of other's copyright material under the Copyright Act 1968 (Cth).